The Influence of Social Commerce Adoption and Visual Content Quality on MSME Sales Performance with Consumer Trust as a Mediating Variable: Penelitian - Bagus Yunianto Wibowo; Irin Mirrah Luthfia; Nanang Adie Setyawan; Destine Fajar Wiedayanti; Mona Inayah Pratiwi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The rapid integration of social media and e-commerce, known as social commerce (s-commerce), has fundamentally reshaped the operational landscape for Micro, Small, and Medium Enterprises (MSMEs). This study investigates the impact of social commerce adoption and visual content quality on the sales performance of MSMEs, with consumer trust serving as a critical mediating variable. In the highly competitive digital market of 2026, MSMEs face the challenge of not only adopting new technologies but also masterfully crafting visual narratives that capture consumer attention. Utilizing a quantitative research design with a sample of 450 MSME owners in Indonesia, this study employs Structural Equation Modeling (SEM-PLS) via SmartPLS 4.0 to analyze the relationships between variables. The results indicate that both social commerce adoption and visual content quality have a significant positive direct effect on MSME sales performance. Furthermore, consumer trust is found to partially mediate these relationships, suggesting that the effectiveness of digital tools and aesthetics is heavily contingent upon the brand's ability to foster a sense of security and reliability among digital consumers. This research provides a strategic roadmap for MSME owners to prioritize high-fidelity visual assets and trust-building mechanisms within their social commerce frameworks to ensure sustainable growth in a volatile digital economy.